Interprofessional Collaboration Between Medical And Nursing Teams To Enhance Quality Of Care For Patients With Chronic Diseases (The Review of Diabetic Studies, 2024)
High-quality chronic-disease care requires active interprofessional collaboration (IPC), defined as team-based practice between professionals who have distinct, yet complementary, roles (Reese et al., 2021). This abstract synthesizes energy-source theory and the theory of interprofessional collaborative practice to highlight three IPC approaches relevant for medical and nursing teams: coordinated care through shared management plans, collaborative care via predefined roles and frequent consultations, and integrated care with joint frameworks, simultaneous input, and collective decision-making. It then presents a synthesis of IPC’s positive clinical impact on chronic-disease-continuity, quality-of-care improvement, patient safety, personalized care, adherence support, shared decision-making, and patient-reported experience. Empowering IPC in chronic disease necessitates interprofessional education for pregraduate students and continual professional development for staff, engendered by interprofessional curricula, simulation, reflective practice, user engagement, implementation science, efficient workflows, and systemic leadership (Gucciardi et al., 2016). Concrete IPC operationalization entails synchronizing multiagency routines, establishing digital-interoperability requirements, leveraging telehealth, and nurturing privacy-conscious, safe-care cultures. By integrating theoretical foundations, practical actions, and contextual considerations, this work delineates a transformative pathway for chronic-disease care—one that remains sustainable amid growing service pressures while aligning with long-term systemic strategies to build capacity, enhance the user interface, and rectify quality-root causes.